Diffuse Pancreatic Mucinous Cystic Neoplasm Treated by Total Pancreatectomy - Chen, Hongyi; Teague, Julie; Weinberg, Laurence; Nikfarjam, Mehrdad (JOP. Journal of the Pancreas, 2015)
Context Multifocal or diffuse mucinous cystic neoplasm are uncommon and may be difficult to distinguish from multifocal intra-ducal mucinous neoplasm or diffuse serous cystadenoma. Case report A forty-seven-year old lady with vague abdominal pain was noted to have cystic lesions ranging from 5 to 20 mm throughout her pancreas. The cysts had enlarged over several years of observation. There was no evidence of pancreatic duct dilatation or communication with the pancreatic duct on magnetic resonance imaging. Cyst fluid analysis for carcinoembryonic antigen and amylase were non-diagnostic. A total pancreatectomy was performed, with histology confirming numerous cysts lined by mucus producing cells, without obvious ovarian-like stroma. The stroma did however demonstrate positive staining for oestrogen receptor and smooth muscle actin. These findings were most consistent with a mucinous cystic neoplasm, despite the apparent absence of typical ovarian like stroma. Conclusion Multifocal or diffuse pancreatic mucinous cystic neoplasm are uncommon and may be suspected when imaging demonstrates multiple pancreatic cysts without communication with the pancreatic duct or pancreatic duct dilation. Surgical resection is indicated due to the increased risk of malignancy. Image: Sectioning of the pancreas demonstrates multiple cysts without any clear communication with the pancreatic duct and no evidence of pancreatic duct dilatation.